Feasibility Assessment of CO2 Capture Retrofitted to an Existing Cement Plant: Post-combustion vs. Oxy-fuel Combustion Technology. (July 2017) - Gerbelová, Hana; van der Spek, Mijndert; Schakel, Wouter
Abstract: This research presents a preliminary techno-economic evaluation of CO2 capture integrated with a cement plant. Two capture technologies are evaluated, monoethanolamine (MEA) post-combustion CO2 capture and oxy-fuel combustion. Both are considered potential technologies that could contribute to reduction of CO2 emissions in the cement industry. The study compares these two technologies in terms of technical performance, investment costs, and operational costs. The case study is applied to the one of the largest cement plants in Portugal, Alhandra. The results show that the amount of CO2 avoided using the post-combustion MEA technology is lower due to additional emissions from reboiler steam production. Moreover, the total capital investment of the post-combustion CO2 capture system is estimated at 260 M€2014 and the annual operation and maintenance costs of around 43 M€2014 ; whereas the oxy-fuel combustion CO2 capture requires a capital investment of about 217 M€2014 and 37 M€2014 annually for operation and maintenance. This indicates that the oxy-fuel CO2 capture technology may be a better choice in terms of costs. However, this technology implies higher technical uncertainties concerning integration with the cement plant.